ISTILAH-ISTILAH KEKERABATAN MASYARAKAT KABUPATEN KEBUMEN: SEBUAH KAJIAN ETNOLINGUISTIK - Ambar Pujiyatno (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2009)
Linguistic anthropology is the discipline studying the language by applying the concepts of culture and anthropology, and trying to explore the tacit meaning underlying the application of the terms. A kinship or familial system is usually implied in the address terms used by the society. This is one of the phenomena under its investigation. It shows how the language in the society and its relation to the cultural phenomenon. The paper tries to explore the phenomenon of kinship system and its language realization in the community of Kebumen Regency. It is to describe the phenomenon and its unique characteristics. The analysis shows that there are 16 generations included in the familial system. They are (1) bapak, rama, ibu, biyung (2) mbah, kaki, nini, eyang (3) buyut, (4) canggah, (5) wareng, (6) udheg-udheg, (7) gantung siwur, dan (8) petarangan bubrah. Generasi ke bawah, yaitu (1) anak, (2) putu, (3) buyut, (4) canggah, (5) wareng, (6) udheg-udheg, (7) gantung siwur, and (8) petarangan bubrah. All are the first direct lineality, which can be extended to the next lineality: uwa, siwa, lilik, bibi, paman, om, tante, kakang, mbekayu, adi, alo, plunan, and ponakan. The third lineality will include misan. The kinship terms are drawn from the blood bond. In reality, the terms are sometimes addressed to an individual beyond the familial relation, for example the terms like lilik, mbah, and om. They are frequently used for addressing a person to show respect, without any meaning that implies the kinship relation.